Creeping Gait Analysis and Simulation of a Quadruped Robot - Raheem, Firas A.; Flayyih, Murtadha Khudhair (Al-Khwarizmi Engineering Journal, 2019)
A quadruped (four-legged) robot locomotion has the potential ability for using in different applications such as walking over soft and rough terrains and to grantee the mobility and flexibility. In general, quadruped robots have three main periodic gaits: creeping gait, running gait and galloping gait. The main problem of the quadruped robot during walking is the needing to be statically stable for slow gaits such as creeping gait. The statically stable walking as a condition depends on the stability margins that calculated particularly for this gait. In this paper, the creeping gait sequence analysis of each leg step during the swing and fixed phases has been carried out. The calculation of the minimum stability margins depends upon the forward and inverse kinematic models for each 3-DOF leg and depends on vertical geometrical projection during walking. Simulation and results verify the stability insurance after calculation the minimum margins which indicate clearly the robot COG (Center of Gravity) inside the supporting polygon resulted from the leg-tips.